Supplier Selection Criteria: A Case in Selecting Best Supplier for Industrialised Building System (IBS) Construction Project - Yaakob, Mazri; Nawi, Mohd Nasrun Mohd; Omar, Mohd Faizal (CENTRAL ASIA AND THE CAUCASUS, 2024)
Supplier selection is the most important activities in construction supply chain, especially in Industrialised Building System (IBS) construction where most of the building component are not manufactured in construction site. There is a need for accurate decision in supplier selection, which is essential nowadays with the increasingly competitive environment. Inaccurate selection could lead to serious construction problems, such as project delay, and cost overrun. Moreover, with the existence high numbers of criteria and suppliers available, the supplier selection process for a specific project needs becoming more difficult. An interview session was conducted among three decision makers (DMs), then selected the relevant and critical criteria and sub-criteria of a IBS supplier that has been identified from various literature. As a result, cost (total cost and term of payment) and capability (design, problem treatment and mobility) are the most influence criteria and sub-criteria that has been highlighted.